Simulações computacionais de moléculas com aplicações em biociências - Suárez, Eduardo Díaz (2015)
In the present work we performed electronic structure calculations within the Kohn-Sham scheme of the density functional theory (DFT). We studied two molecules with potential applications in life sciences and medicine: ferrioxamine B and 5,10,15,20-tetrakis(1-methyl-4-pyridyl)-21H,23H (TMPyP) porphyrin. We used different methods and different exchange and correlation functionals, analyzing optical and vibrational properties and hyperfine interactions. In the case of ferrioxamine B, results in the crystalline phase (molecular crystal), and gas phase were compared with experimental results obtained using Mössbauer spectroscopy from the literature. We analyzed hyperfine parameters such as the electric quadrupole splitting, asymmetry parameter, hyperfine field and isomer shift. In the case of TMPyP porphyrin we analyzed vibrational properties in the gas phase and optical properties. For the electronic absorption, solvent effects and electronic charges states were analyzed.